Postconference Digest Quantum Electronics and Laser Science, 2003. QELS. 2003
DOI: 10.1109/qels.2003.237898
|View full text |Cite
|
Sign up to set email alerts
|

Controllable frequency entanglement via auto-phase-matched spontaneous parametric down-conversion

Abstract: A new method for generating entangled photons with controllable frequency correlation via spontaneous parametric down-conversion (SPDC) is presented. The method entails initiating counter-propagating SPDC in a single-mode nonlinear waveguide by pumping with a pulsed beam perpendicular to the waveguide. 02002 Optical Society of America OCIS codes: (270.0270) Quantum opticsIn a typical spontaneous parametric down-conversion (SPDC) experiment, a photon from a monochromatic pump beam decays into two photons (often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Care must be taken, however, to ensure that the intrinsic quantum correlations between the twin photons are eliminated so that the surviving photon is in a pure state [45][46][47]. One way of achieving this is to generate the twin photons with a factorable joint amplitude [48][49][50][51]. We have previously shown that a Type-0 interaction could be used to generate photon pairs that are degenerate in frequency and polarization, but with opposite mode number [2,Sec.…”
Section: Modal Qubitsmentioning
confidence: 99%
“…Care must be taken, however, to ensure that the intrinsic quantum correlations between the twin photons are eliminated so that the surviving photon is in a pure state [45][46][47]. One way of achieving this is to generate the twin photons with a factorable joint amplitude [48][49][50][51]. We have previously shown that a Type-0 interaction could be used to generate photon pairs that are degenerate in frequency and polarization, but with opposite mode number [2,Sec.…”
Section: Modal Qubitsmentioning
confidence: 99%
“…Non-collinear SPDC also allows the control of the generation of frequency-uncorrelated photons by controlling the pump-beam width and the angle of emission of the down-converted photons [11,12]. It is indeed possible to map the spatial characteristics of the pump beam into the spectra of the generated photons (spatial-to-spectral mapping) [13], thus providing another way to manipulate the joint spectral amplitude of the biphoton, as has been demonstrated in [14].…”
Section: Introductionmentioning
confidence: 99%